PREPARATION OF GLASS-CERAMIC FROMSODA LIME WASTE GLASS - Abdullah, Siham S (Al-Nahrain Journal of Science, 2018)
The waste soda lime glass was converted to glass-ceramic by adding certain amounts of alumina, lithium oxide and titanium oxide. The effect of quenching in air on the microstructure and the mechanical properties were investigated. SEM observations clearly revealed that the presence of homogeneously dispersed tiny single crystals with average size of 4μm for quenching sample which increased with holding time at the nucleation temperature of 650°C to reach a maximum size of 10μm. The results of Vickers hardness tests indicate that the hardness value of the as quench soda lime based glass-ceramic is 724 kg/mm2 . This value starts to decrease with increasing holding time at nucleation temperature to reach 687 kg/mm 2 after 96 h for the crystals growth.